2014
DOI: 10.1038/srep07581
|View full text |Cite
|
Sign up to set email alerts
|

Dual sgRNA-directed gene knockout using CRISPR/Cas9 technology in Caenorhabditis elegans

Abstract: The CRISPR RNA-guided Cas9 nuclease gene-targeting system has been successfully used for genome editing in a variety of organisms. Here, we report the use of dual sgRNA-guided Cas9 nuclease to generate knockout mutants of protein coding genes, noncoding genes, and repetitive sequences in C. elegans. Co-injection of C. elegans with dual sgRNAs results in the removal of the interval between two sgRNAs and the loss-of-function phenotype of targeted genes. We sought to determine how large an interval can be elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
131
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 58 publications
(87 reference statements)
3
131
0
2
Order By: Relevance
“…Interestingly, these species have different modes of reproduction (C. briggsae, androdioecy vs. C. nigoni, gonochoristic) but can produce fertile hybrid progeny (Woodruff et al 2010), suggesting that H3K9me2 and H3K9me3 are interchangeable for X chromosome silencing. These findings are also in concordance with functional analyses of the chromatin remodeling NURF complex, where NURF is required for the sperm/oocyte decision in C. briggsae but not in C. nigoni (Chen et al 2014). Thus, germ-line chromatin marks have the capacity to evolve rapidly.…”
Section: H3k9me2 Vs H3k9me3supporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, these species have different modes of reproduction (C. briggsae, androdioecy vs. C. nigoni, gonochoristic) but can produce fertile hybrid progeny (Woodruff et al 2010), suggesting that H3K9me2 and H3K9me3 are interchangeable for X chromosome silencing. These findings are also in concordance with functional analyses of the chromatin remodeling NURF complex, where NURF is required for the sperm/oocyte decision in C. briggsae but not in C. nigoni (Chen et al 2014). Thus, germ-line chromatin marks have the capacity to evolve rapidly.…”
Section: H3k9me2 Vs H3k9me3supporting
confidence: 77%
“…Alternatively, Cbr-met-2(RNAi) may have had off-target effects, resulting in removal of both H3K9me2 and H3K9me3. To distinguish between these possibilities, we generated deletion mutations of Cbr-met-2 using clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 with dual sgRNAs as described for C. elegans (Chen et al 2014) (Figure 5A). We isolated two independent deletions: Cbr-met-2(xoe1) and Cbr-met-2(xoe2).…”
Section: The X Chromosome Of Males Is Enriched For Different Repressimentioning
confidence: 99%
“…The initial report describing the successful use of Cas9 in C. elegans demonstrated a range of editing frequencies from 0.5 to 80%, with only two targets exceeding 4% . Subsequent publications also reported variably low mutagenesis rates that required molecular screening of hundreds of animals or required the desired mutation to cause an easily detectable mutant phenotype or to be introduced in tandem with a coselection marker (Chiu et al 2013;Cho et al 2013;Dickinson et al 2013;Katic and Grosshans 2013;Lo et al 2013;Tzur et al 2013;Waaijers et al 2013;Chen et al 2014;Liu et al 2014;Paix et al 2014;Shen et al 2014;Zhao et al 2014). More recent studies greatly improved the odds of detecting a targeted mutation through the simultaneous co-conversion of a mutation in an unrelated target that causes a visible phenotype (Arribere et al 2014;Kim et al 2014;Ward 2014).…”
mentioning
confidence: 99%
“…However, there are no reports concerning Cas9-mediated genome rearrangements in C. elegans. Our previous work showed that large chromosome fragments of up to 24 kb can be eliminated through the co-injection of two sgRNAs in C. elegans (Chen et al 2014). Here, we report the use of dual sgRNA-guided Cas9 nuclease to direct reciprocal chromosomal translocations in C. elegans.…”
mentioning
confidence: 99%
“…sgRNA #2 targeting exon 2 of the dpy-13 gene exhibited the highest efficiency and was used in the translocation experiments. For rde-12, the sgRNA targeting exon 2 of rde-12 was previously reported to have a high cleavage efficiency (Chen et al 2014) and was used in this work.We co-injected sgRNAs targeting rde-12 and dpy-13 with Cas9 and mCherry expression plasmids into eri-1(mg366) animals ( Figure S2). The mutation of eri-1 results in an enhanced RNAi (Eri) phenotype that facilitates the analysis of …”
mentioning
confidence: 99%